2014
DOI: 10.1088/0004-637x/796/2/89
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Ram-Pressure Stripping With Warm Molecular Hydrogen Emission

Abstract: We use the Spitzer Infrared Spectrograph to study four infalling cluster galaxies with signatures of ongoing rampressure stripping. H 2 emission is detected in all four, and two show extraplanar H 2 emission. The emission usually has a warm (T ∼ 115-160 K) and a hot (T ∼ 400-600 K) component that is approximately two orders of magnitude less massive than the warm one. The warm component column densities are typically 10 19 to 10 20 cm −2 with masses of 10 6 to 10 8 M . The warm H 2 is anomalously bright compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Enhanced X-ray emission outside NGC 2276, and the bowshock feature on the western edge of NGC 2276's disk was attributed to ram pressure (Rasmussen et al 2006) as similar features have been observed in galaxies with ongoing ram pressure (Iglesias-Paramo & Vilchez 1997;Sivanandam et al 2014;Troncoso Iribarren et al 2016). The high ram pressure acting on NGC 2276 is linked to the unusually high density of the group's inter-galactic medium .…”
Section: Introductionmentioning
confidence: 69%
“…Enhanced X-ray emission outside NGC 2276, and the bowshock feature on the western edge of NGC 2276's disk was attributed to ram pressure (Rasmussen et al 2006) as similar features have been observed in galaxies with ongoing ram pressure (Iglesias-Paramo & Vilchez 1997;Sivanandam et al 2014;Troncoso Iribarren et al 2016). The high ram pressure acting on NGC 2276 is linked to the unusually high density of the group's inter-galactic medium .…”
Section: Introductionmentioning
confidence: 69%
“…The dust could be stripped concurrently as spiral galaxies are likely to contain diffuse ionized gas in their halo that is associated with the presence of dust (Howk & Savage 1999;Ménard et al 2010). Moreover, observational evidence for dust stripping in galaxies with likely ongoing ram-pressure stripping has been detected (Crowl et al 2005;Cortese et al 2010a;Sivanandam et al 2014). Therefore, the warmer dust component could be removed with the gas, along with the cool dust associated with the HI (Boselli & Gavazzi 2006;Cortese et al 2010b).…”
Section: A Simple Interpretation For Quenchingmentioning
confidence: 99%
“…Increasing AGN feedback from a growing supermassive black hole may shock or eject gas from the galaxy disk, reducing its capacity to form stars (Hopkins et al 2006;Ogle, Lanz, & Appleton 2014). Ram-pressure stripping of the interstellar medium (ISM) by the intercluster medium (ICM) of a galaxy cluster can also remove cold gas (Sivanandam, Rieke, & Rieke 2014).…”
Section: Introductionmentioning
confidence: 99%